Numerical Simulation of Convective Heat Transfer in Gyroid, Diamond, and Primitive Microstructures Using Water as the Working Fluid - Jie Zhang; Xiaoqing Yang (Energies)
With the continuous increase in the thermal power of electronic devices, air cooling is becoming increasingly challenging in terms of meeting heat dissipation requirements. Liquid cooling media have a higher specific heat capacity and better heat dissipation effect, making it a more efficient cooling method. In order to improve the heat dissipation effect of liquid cooling, a TPMS structure with a larger specific surface area, which implicit function parameters can control, can be arranged in a shape manner and it is easy to expand the structural design. It has excellent potential for application in the field of heat dissipation. At present, research is still in its initial stage and lacks comparative studies on liquid cooled convective heat transfer of TPMS structures G (Gyroid), D (Diamond), and P (Primitive). This paper investigates the heat transfer performance and pressure drop characteristics of a sheet-like microstructure composed of classic TPMS structures, G (Gyroid), D (Diamond), and P (Primitive), with a single crystal cell length of 2π (mm), a cell number of 1 × 1 × 5, and a microstructure size of 2π (mm) × 2π (mm) × 22π (mm) using a constant temperature surface model. By analyzing the outlet temperature <semantics>tout</semantics>, structural pressure <semantics>p</semantics>, average convective heat transfer coefficient <semantics>h0</semantics>, Nusselt number <semantics>Nu</semantics>, and average wall friction factor <semantics>f</semantics> of the microstructure within the speed range of 0.01–0.11 m/s and constant temperature surface temperature is 100 °C, the heat transfer capacity D > G > P and pressure drop D > G > P were obtained (the difference in pressure drop between G and P is very small, less than 20 Pa, which can be considered consistent). When flow velocity is 0.01 m/s, the maximum temperature difference at the outlet of the four structures reached 17.14 °C, and the maximum difference in wall friction factor <semantics>f</semantics> reached 103.264, with a relative change of 646%. When flow velocity is 0.11 m/s, the maximum pressure difference among the four structures reached 8461.84 Pa, and the maximum difference in <semantics>h0</semantics> reached 7513 W/(m2·K), with a relative change of 63.36%; the maximum difference between Nu reached 76.32, with a relative change of 62.09%. This paper explains the reasons for the above conclusions by analyzing the proportion of solid area on the constant temperature surface of the structure, the porosity of the structure, and the characteristics of streamlines in the microstructure.